Pore Pressure Prediction of an Oil-Field in Part of the Niger Delta Basin, Nigeria - F.I. Chiazor; F.T. Beka (Journal of Applied Sciences and Environmental Management)
In this study, overpressure prediction was carried out for ten oil wells in a selected oil-field in part of the Niger Delta basin, Nigeria. The age of key stratigraphic surfaces (9.5Ma-65Ma), depth, thickness and sedimentation rates from well logs and biostratigraphic data was used to build pressure models. The generated pressure model was calibrated using key  petrophysical, geochemical and pressure data until a match was achieved. The model predicts occurrence of localized under-compaction driven overpressure at about 11.5Ma. From the results, the onset of overpressure is likely at depths beyond 14,760ft which corresponds to the 11.5Ma marker shales, while fluid pressures ranging from 0.53-0.7psi/ft are estimated at 15,744ft and hard overpressures ranging from 0.7-0.9psi/ft are likely at depths beyond 19,680ft which corresponds to the 12.8Ma marker shales. This study provides good prediction on the occurrence of pressure in the deeper prospect.